2.5–5.5 μm mid‐infrared emission from Ni2+‐doped chalcohalide glass ceramics containing CsPbI3 perovskite nanocrystals. Issue 11 (22nd June 2021) - Cui, Manman; Yang, Anping; Sun, Mingyang; Lin, Huixing; Lin, Hang; Ren, Jing; Yang, Zhiyong
Abstract: The development of mid‐infrared (MIR) broadband tunable lasers urgently needs high performance laser gain materials. Transition metal (TM) ions doped glass ceramics are considered to be efficient MIR broadband laser gain media. However, it is difficult to achieve gain because of the large scattering loss and low luminescence efficiency. In this paper, GeS2 –Sb2 S3 –CsI–PbI2 chalcohalide glass ceramics containing CsPbI3 perovskite nanocrystals are fabricated by the melt‐quenching method and subsequent heating treatment. The crystallization behavior of CsPbI3 nanophase and MIR luminescence properties of Ni 2+ dopant are systematically investigated. Evidently, spherical CsPbI3 perovskite nanocrystals are precipitated and uniformly distributed in the glassy matrix, which can reduce the light scattering and make the chalcohalide glass ceramics have a high transparency. Moreover, an ultra‐broadband MIR emission in the range of 2.5–5.5 μm is observed for the first time, to our best knowledge, from Ni 2+ ‐doped chalcohalide glass ceramics containing CsPbI3 perovskite nanocrystals. The newly developed Ni 2+ ‐doped chalcohaldie glass ceramics could be promising gain media for MIR broadband tunable lasers.